Web information system engineering WISE 2011 12th International Conference, Sydney, Australia, October 13-14, 2011 : proceedings - Bouguettaya, Athman; Hauswirth, Manfred; Liu, Ling 1960- (Lecture Notes in Computer Science, 2011)
This book constitutes the proceedings of the 12th International Conference on Web Information Systems Engineering, WISE 2011, held in Sydney, Australia, in October 2011. The 17 revised full papers and 11 revised short papers presented together with 7 demo papers were carefully reviewed and selected from 96 submissions. The papers contained in these proceedings address challenging issues in software services, Web application engineering and modelling, Web search, social networks, Web semantics, and information retrieval and extraction.